Orphan Drug Prices and Epidemiology of Rare Diseases: A Cross-Sectional Study in Italy in the Years 2014–2019 - Villa, Federico; Di Filippo, Aurora; Pierantozzi, Andrea; Genazzani, Armando; Addis, Antonio; Trifirò, Gianluca; Cangini, Agnese; Tafuri, Giovanni; Settesoldi, Daniela; Trotta, Francesco (Frontiers in Medicine, 2022)
IIntroduction: It is well acknowledged that the price of orphan drugs is normally higher than that resulting from the value-based pricing. A correlation between the cost of therapy for orphan drugs and the epidemiology (prevalence and incidence) of the related rare disease can be hypothesized. Methods: This analysis includes all approved orphan drugs by European Medicines Agency whose reimbursement was granted for the first therapeutic indication in the years 2014-2019 in Italy. Regression and correlation analyses were performed to analyze the possible correlations between the logarithm of the annual therapy cost and the epidemiology of the rare diseases, between orphan drugs consumption and epidemiology of related rare disease and between therapy cost and the consumption. Results: The regression analysis between the annual cost of therapy estimated on the published ex-factory price and the prevalence showed a slightly decreasing, not statistically significant, trend (coefficient: -0.10, p-value: 0.41). The results were similar when using the price resulting from the application of Managed Entry Agreements (coefficient: -0.11, p-value: 0.40). The regression analysis between sales volume and prevalence showed a positive slope without an acceptable level of significance (p-value: 0.04). The correlation analysis between the therapy cost and the sales volume highlighted again an absence of significant association, similarly if considering only ATC L orphan drugs, or the incidence.